Chemical Constituents and Bioactivities of Azanza garckeana: A Review - Titus, Stephen Dio; Christian, Nelson; Samuel, Kennedy B.; Ishaya, Samuel G.; Francis, Achilus; Leyoa, Ajiduku Abershi (Darul Yasin Al Sys, 2025)
Azanza garckeana, commonly known as